Public procurements and circular economy - Recommendations for decision-makers and procurement managers - Yliruusi, Hannamaria; Lankiniemi, Sonja; Alhola, Katriina (Turun ammattikorkeakoulu, 2024)
Public procurements and circular economy – Recommendations for decision-makers and procurement managers – The publication concisely compiles recommendations for decision-makers and procurement managers to support the promotion of circular economy procurements. The publication summarizes the results of a municipal survey conducted within the Circwaste – Towards circular economy in Finland project in a concise and concrete manner. The survey highlighted that an organization must commit to promoting the circular economy at a strategic level and recognize the role of procurement in achieving the organization’s circular economy goals. It is also necessary to ensure that the circular economy is integrated into practical procurement activities. The publication presents four critical factors identified in the study that support the practical implementation of circular economy procurements: • Strategic leadership. Procurements must be managed strategically and systemically, focusing on the most effective procurement categories. • Communication. Procurements must be communicated both externally and internally, so that the new methods and benefits are widely spread. • Increasing competence. Those carrying out procurements must know the principles of circular economy procurement. Circular economy changes the traditional procurement approach, and the importance of needs assessment is highlighted. • Monitoring and impact. Circular economy procurements must be able to be monitored and impact assessed. The municipalities that participated in the study were Jyväskylä, Kuopio, Lahti, Lappeenranta, Porvoo, Riihimäki, Rovaniemi, Ii, Turku, Vantaa, and Pori. The publication is part of the Circwaste – Towards circular economy in Finland project and has received funding from the European Union’s LIFE program.